Investigating meningitis in cases of sudden and unexpected death in infancy (SUDI) at the Tygerberg Medico-legal Mortuary in the Western Cape Metropole - Nortjé, Simoné-Odette (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.